In vitro Propagation of Watermelon (Citrullus valgaris) - Khanam, D; Malek, MA; Khatun, MM; Molla, MMH; Al-Amin, M (Bangladesh Journal of Genetics and Biotechnology, 2009)
Keywords: In vitro culture; Citrullus valgaris; shoot tip; nodal segment Bangladesh j. genet. biotechnol. 7 (1&2): 95-97, 2006 (June & December)